Una concepción transductiva del cambio social: discapacidad, agentes, cuerpos y emociones - Ferreira, Miguel A. V. (Nómadas. Critical Journal of Social and Juridical Science, 2011)
From its first steps, sociological thinkingi prisoner of Ilustration mape dicotomies. Subject and object as its primarly mannifestation, and Comte proposal, distinguishing “static” form “dinamic” as a first enunciation; structure against change. But social change, as an space of reflection, interchange this fundational dicotomie with another one, contradictory with it, the one which places change, as a structural thing, against agency, action, as a singular phemomenum. This contradiction provides the oportunity to re-reflect on our fundational epistemological key criteria. Whe propose a “procesual principle”: hcange is the “ontos”, and from its permanent irresolution merges our existence; the “being” is a philosofical fiction; in addition, the “individual”, as a political categorie, in a first place, and a sociologícal one, in a second plane, also. We have lost the “person” (the human one), in its whoe constitution and in its social conformation. It becomes neccesary to rescue the person from that reified categories (subject, individual and citizen) and replace it in its proper condition. To do that, the body has to be stated in a main place (our animal condition, social conformed and conformational), and, with it, our emotions (the irrational basis of our rationality). Some kind of “persons” who are in conditions to do this are persons with disability (ther are more than a person in their daily life, but are less than a person under the categories putted in cuestion —subject, individual, citizen—). We need an epistemological reconfiguration, that means to change a disabling and disbled world in another one in which body and emotions have the main plece they have to have. Perhaps is now the time to make appear our collective reppressed inconscience.